Quality Improvement of White Pepper with Processing through Optimizing the Ratio of Starter Culture from Acetobacter sp., Bacillus subtilis, and Bacillus cereus - Kirana Sanggrami Sasmitaloka; Hernani Hernani (Bogor Agricultural University, Indonesia, 2022)
Fermentation process using known microbial species can be exploited for the processing of white pepper. It is expected to generate quality of white pepper in a short period soaking time. This research aimed to study characteristics of white pepper through a fermentation process by addition of combination isolates of Acetobacter sp., B. subtilis, and B. cereus. After threshing, 2 kg of fresh pepper berries was soaked in water mixed with starter culture. The experiment used a completely randomized design, two replications. The treatment consisted of: A) starter culture ratio of Acetobacter sp.: B. subtillis: B. cereus (A1 = 0:0:0; A2 = 1:1:1; A3 = 2:1:1; A4 = 1:2:1; and A5 = 1:1:2) and soaking time (B1 = 5 and B2 = 7 days). Fermented pepper was decorticated, washed, and dried. The best treatment was fermented for 7 days with the combination isolates of Acetobacter sp., B. subtilis, and B. cereus with ratio 2:1:1. This condition produced white pepper in fulfilling in requirement of SNI standards with piperine and essential oil contents and TPC of 5.95%, 2.95% and 1.1 x 102 CFU/g, respectively. This process is expected to generate high quality of white pepper in a short soaking time.